2015
DOI: 10.1177/1071100715571439
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Column Lengthening Corrects Hindfoot Valgus in a Cadaveric Flatfoot Model

Abstract: Understanding the relative contribution of each operative procedure to the overall deformity correction in flatfoot reconstruction will allow surgeons to accurately correct the foot into a plantigrade position while minimizing the risk of overcorrection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…All the patients and their parents were satisfied with the functional outcomes (Table 1 Some authors previously observed that LCL or double calcaneal osteotomy was optimal for severe forefoot abduction deformity and also better realigned the midfoot transverse plane deformities [5,9,17]. A cadaveric study also reported that LCL can restore 60% of hindfoot valgus deformities associated with 100% forefoot abduction deformity [18]. In the current study, there were 16 feet that underwent LCL and 13 feet that underwent double calcaneal osteotomy.…”
Section: Resultssupporting
confidence: 53%
“…All the patients and their parents were satisfied with the functional outcomes (Table 1 Some authors previously observed that LCL or double calcaneal osteotomy was optimal for severe forefoot abduction deformity and also better realigned the midfoot transverse plane deformities [5,9,17]. A cadaveric study also reported that LCL can restore 60% of hindfoot valgus deformities associated with 100% forefoot abduction deformity [18]. In the current study, there were 16 feet that underwent LCL and 13 feet that underwent double calcaneal osteotomy.…”
Section: Resultssupporting
confidence: 53%
“…In other cadaveric studies of ankle biomechanics, fresh specimens were often fixed on an experimental frame or to a test bench with a Kirschner wire 10 20 21 22 . However, even if a person stands still, the foot joints slide and rotate slightly to balance the body’s weight 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This foot position was prescribed using an aluminum wedge with a 10°slope. The 12 test conditions were loaded based on a previously described loading regime [3,20]: a 400-N ground reaction force was achieved and maintained from an axial load applied along the axis of the tibia and a 350-N tensile load along the Achilles tendon through a pneumatic cylinder (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%